Soaking Feet Therapy with Ginger on Elderly with Arthritis: Case Study - Pratiwi, Dinda Nur; Wahyudi, Iwan (CV. Literasi Publikasi Indonesia, 2023)
Osteoarthritis, also known as degenerative joint disease, is a condition where the joints feel painful due to mild inflammation caused by friction between the bones that make up the joint. It is a slow-progressing disease with different causes, and it is more common in women aged 60 years and over. There is currently no cure for osteoarthritis, and management is mainly aimed at controlling pain, improving joint movement and function. This case was to analyze nursing care for clients with osteoarthritis with the main intervention applying warm compress therapy boiled with ginger to reduce pain. Using a case study with an osteoarthritis client which was carried out for three consecutive days for 15 minutes per day. The results of the intervention carried out on osteoarthritis clients with chronic pain problems before being given warm compress therapy with boiled ginger, the pain scale was at 5 (moderate pain) from a range of 0-10, after being given warm compress therapy with boiled ginger, the pain scale was reduced to 3. (mild pain). Warm compress therapy boiled with ginger has been shown to have a significant effect on reducing pain in osteoarthritis patients.